2021
DOI: 10.1016/j.whi.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Concerns About the Cost of Contraception Among Young Women Attending Community College

Abstract: had full access to the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Affordability of contraception has been shown to be a common concern among young people regardless of their health insurance status, so information on low or no-cost services is important in this age group. 13 During the COVID-19 pandemic, barriers to reproductive health services increased, especially for historically marginalized populations. [54][55][56] While access improved somewhat over time and telemedicine visits increased, challenges remained among young people, including those facing basic needs adversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affordability of contraception has been shown to be a common concern among young people regardless of their health insurance status, so information on low or no-cost services is important in this age group. 13 During the COVID-19 pandemic, barriers to reproductive health services increased, especially for historically marginalized populations. [54][55][56] While access improved somewhat over time and telemedicine visits increased, challenges remained among young people, including those facing basic needs adversity.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Many come from non-English-speaking households, face economic adversity, and have cost concerns about accessing care. [12][13][14][15] This study examined data from young women, including cisgender and gender non-binary individuals, in community college. By using data from a community setting, this study includes the experiences of young people in need of care who may have not yet sought care in a clinic, unlike a clinic-based sample that would miss them.…”
Section: Introductionmentioning
confidence: 99%
“…However, even in states with more expansive health coverage policies for both the insured and uninsured, young adults, including students, may still have cost concerns. A study of community college students aged 18–25 in California and Oregon found that nearly half of students were concerned about the cost of contraception, and that the uninsured had the highest cost concerns [ 25 ].…”
Section: Introductionmentioning
confidence: 99%